CORPORATE SOCIAL RESPONSIBILITY BUKAN SEKEDAR KOSMETIK BELAKA - Adriyanto, Irsad (Jurnal Ilmiah Infokam, 2008)
Corporate Social Responsibility (CSR) is considered to improve the corporate image. This is possible because the community served with sweet and information that led to the assumption that firms tend to be very supportive of social life and very concerned about the environment. But beside that, there are many companies that use CSR simply to help smooth business processes. Part given to corporate social responsibility is only a very small part compared with a profit from the business process. Expected future CSR actually become the company form of concern that resulted in either a positive synergy with the environment as well as with countries in general.Keywords: social responsibility, business processes.